Pengaruh Cash Flow Volatility, Firm Size, Foreign Debt dan Exchange Rate terhadap Hedging (Studi pada Perusahaan Sektor Energi Tahun 2018-2022) - Hadini, Chila Ratna; Desmiza, Desmiza (J-MAS (Jurnal Manajemen dan Sains), 2024)
The energy sector has a sharp increase in the value of imports resulting in a trade deficit that causes losses for the country as the rupiah depreciates against the exchange rate. This makes the energy sector vulnerable to exchange rate risk. Any hedging instruments such as swaps, options, forwards & options and natural hedging are generally used by companies to protect foreign exchange exposures. This study aims to examine the effect of Cash Flow Volatility (CFV), Firm Size (SIZE), Foreign Debt (FD) and Exchange Rate (ER) on the use of hedging using various instruments used by companies. By using purposive sampling, 35 energy sector companies in 2018-2022 samples were chosen for the study, and data were gathered from annual repots available on the Indonesia Stock Exchange website. The analysis employed aims to examine the impact of independent variables on the dependent in this study is logistic regression analysis. The results of this study prove that cash flow volatility, firm size and foreign debt have a positive and significant effect on hedging. While the exchange rate has no effect on hedging. The coefficient value of determination in which the variation of the dependent variable can be explained eh the variability of independent variables by 17 percent.